Strategi Pemasaran Produk Gadai Emas Pada PT. Pegadaian Simpang Empat Pasaman Barat - Manik Santia; Fajar Budiman; Yossi Eriawati (Universitas 45 Surabaya, 2023)
The background of this research is in Jorong Simpang Empat, Pasaman District, West Pasaman Regency. The main problem in this study is related to the Marketing Strategy for Pawn Gold Products at PT. Simpang Empat Pawnshop West Pasaman. Furthermore, the problem is divided into several formulations, namely: 1) What is the Marketing Strategy for Pawn Gold Products at PT. Pegadaian Simpang Empat Pasaman Barat, 2) What is the Strategy for Maintaining the Number of Customers at PT. West Pasaman Simpang Empat Pawnshop. This study aims to gain an understanding of how the marketing strategy for gold pawning products is theoretically or practically applied by PT. Pegadaian Simpang Empat West Pasaman and know more about how the development of gold pawning at PT. West Pasaman Simpang Empat Pawnshop. This study uses field research methods (field research), the type of approach is qualitative. The data sources for this research are the leaders and employees of PT. West Pasaman Simpang Empat Pawnshop. The data collected in this study are primary data and secondary data. This primary data was obtained through interviews with informants, namely PT. Pegadaian is the head of PT Pegadaian Simpang Empat, West Pasaman. The results showed that the strategy carried out by PT Pegadaian Simpang Empat Pasaman Barat in increasing the number of its customers was carried out with the 4P strategy, namely product strategy, price strategy, place strategy, and strategy in the field of promotion (promotion). While the strategy to maintain customer levels is carried out by providing good service, namely providing discounts or promos, providing excellent service, digital pawnshops, and extraordinary seminars.